The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.tim.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Infection’s Sweet Tooth: How Glycans Mediate Infection and Disease Susceptibility

Abstract: Glycans form a highly variable constituent of our mucosal surfaces and profoundly affect our susceptibility to infection and disease. The diversity and importance of these surface glycans can be seen in individuals who lack a functional copy of the fucosyltransferase gene, FUT2. Representing around one-fifth of the population, these individuals have an altered susceptibility to many bacterial and viral infections and diseases. The mediation of host-pathogen interactions by mucosal glycans, such as those added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 92 publications
3
49
1
Order By: Relevance
“…HIEs provide an excellent tool for future studies on intestinal enzymes involved in glycosylation and how glycosylation alters glycoprotein localization. An association of enteric commensals and pathogens with host secretor status has led to increased recognition of secretor glycans being susceptibility factors important in infection and disease outcomes (30,31). The exact role played by the glycans in these infections is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…HIEs provide an excellent tool for future studies on intestinal enzymes involved in glycosylation and how glycosylation alters glycoprotein localization. An association of enteric commensals and pathogens with host secretor status has led to increased recognition of secretor glycans being susceptibility factors important in infection and disease outcomes (30,31). The exact role played by the glycans in these infections is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of the α1,2-fucosylated HMOs and soluble α1,2-fucosylated HMGs in non-secretor mothers' milk is responsible for absence of inhibition of the adhesion of α1,2-fucose dependent pathogens to the epithelial host cells (Figure 4a). In the presence of α1,2-fucosylated HMOs and soluble α1,2-fucosylated HMGs in secretor mothers milk the adhesion of α1,2-fucose dependent pathogens to the epithelial host cells is blocked (Figure 4b) [117].…”
Section: Dietary Fucosylated Hmos and Hmgs Have Anti-adhesive Propertiesmentioning
confidence: 99%
“…The lack of the α1,2-fucosylated HMOs and soluble α1,2-fucosylated HMGs in non-secretor mothers' milk is responsible for absence of inhibition of the adhesion of α1,2-fucose dependent pathogens to the epithelial host cells (Figure 4a). In the presence of α1,2-fucosylated HMOs and soluble α1,2-fucosylated HMGs in secretor mothers milk the adhesion of α1,2-fucose dependent pathogens to the epithelial host cells is blocked (Figure 4b) [117]. It has been shown that 2ʹ-FL and additionally 3ʹ-SL can reduce the incidence of viral infections caused by respiratory syncytial virus (RSV) in vitro by significantly reducing RSV viral load and the level of cytokines in the airway epithelium [119].…”
Section: Dietary Fucosylated Hmos and Hmgs Have Anti-adhesive Propertiesmentioning
confidence: 99%
See 2 more Smart Citations